Innovation Experiment in Making Dengue Food Using Cassava Leaves (Manihot Esculenta) as a Substitution Beef - Nur Al-faida; Sukriadi Sukriadi; Irawati Irawati; Mia Mariana Mote; Yaningsi Novita; Amos Edowai (International Journal of Public Health, 2024)
Cassava is a staple food source that is abundant in Indonesia. Cassava leaves have been known to our people for a long time as an alternative vegetable to replace most vegetables in general. For those who are used to it, cassava leaves are a unique vegetable, and can stimulate your appetite, but for those who have never tasted it, it may take time to get used to it. The texture of cassava leaves is rough, so they are only suitable for cooking in a few ways. The aim of this research is to find out the most preferred formula for making beef jerky from cassava leaves. This research is experimental research with the research design used, namely Pre-Experimental Design with a One-shot case study type of research. Based on the research that has been carried out, the conclusion in this study is that of the 4 treatments given, it is seen from the color aspect that the most preferred treatment is P12 (100%), the taste aspect of the treatment is P12 986.7), the aroma aspect is P11 (80%) and the P12 texture (83.3%). For further research, it is hoped that variables such as water content and HCN can be added to cassava leaves.